Clinicopathological and molecular features between synchronous and metachronous metastases in colorectal cancer - Lan, Yuan-Tzu (Am J Cancer Res, 2021)
The molecular difference between synchronous and metachronous metastases in colorectal cancer (CRC) remains unclear. Between 2000 and 2010, a total of 492 CRC patients were enrolled, including 280 with synchronous metastasis and 212 with metachronous metastasis. Clinicopathological and molecular features were compared between the two groups. Patients with synchronous metastasis were more likely to have right-sided CRC, poorly differentiated tumors, lymphovascular invasion, advanced pathological tumor (T) and node (N) categories, and liver metastases than those with metachronous metastasis. For right-sided CRC, patients with synchronous metastasis had more lymphovascular invasion and liver metastases than those with metachronous metastasis. For left-sided CRC, patients with synchronous metastasis were more likely to have poorly differentiated tumors, lymphovascular invasion, advanced pathological T and N categories, and liver metastases than those with metachronous metastasis. Regarding the genetic mutations, patients with metachronous metastasis had more mutations in TP53, NRAS, and HRAS and fewer mutations in APC than those with synchronous metastasis; for right-sided CRC, synchronous metastasis was associated with more APC mutations than metachronous metastasis, while for left-sided CRC, metachronous metastasis was associated with more TP53 and NRAS mutations than synchronous metastasis. The 5-year overall survival (OS) rates were significantly higher in metachronous metastasis patients than in synchronous metastasis patients, especially those with left-sided CRC. Multivariate analysis showed that age, sex, lymphovascular invasion, pathological N category, metachronous metastasis, and BRAF and NRAS mutations were independent prognostic factors affecting OS. CRC patients with synchronous metastasis had a worse OS than those with metachronous metastasis and exhibited distinct genetic mutations.